Pimitamon: Conceptualizing a New Canadian North through the Graphic Narratives of Jeff Lemire - Beard, David; Moffatt, John (Nordlit, 2020)
In Essex County, in Secret Path (his collaboration with Gord Downie), in Roughneck, and in his creation of the indigenous Canadian superhero Equinox for Justice League United: Canada, Jeff Lemire highlights a vision of the Canadian ‘north’ as transformative space. In Lemire’s hands, ‘the north’ is where Chanie Wenjack’s historical reality (Secret Path), Derek and Beth Ouelette’s personal demons (Roughneck), and Miiyahbin Marten’s life as an ordinary indigenous teen in Moose Factory, Ontario (Justice League United Volume 1: Justice League Canada) all undergo a transformation which speaks to shifting perceptions of identity, responsibility, and belonging in Canada. The north becomes a site where Lemire (and Lemire’s readers) directly confront how even a deliberate act of intended reconciliation between settler-colonial and indigenous peoples can effectively colonize the space in which it occurs. All three works, in different ways, deploy rhetorical strategies to minimize the ‘collateral damage’ that is probably unavoidable, and even perhaps necessary, in the articulation of the kind of anticolonial dialogue toward which Lemire’s work is oriented.
Keywords: Settler-colonial studies; Jeff Lemire; Canada; Rhetoric; Crossroads; Indigenous studies